Clinical outcomes of implants placed in ridge‐preserved versus nonpreserved sites: A 4‐year randomized clinical trial. (11th October 2018) - Marconcini, Simone; Giammarinaro, Enrica; Derchi, Giacomo; Alfonsi, Fortunato; Covani, Ugo; Barone, Antonio
Abstract: Background: Consistent bone changes occur after tooth removal, often compromising the success of implants placed within the socket left to natural healing The long‐term effect of ridge preservation on implant outcomes is still unclear. Purpose: The aim of the study was to assess success and survival rates of implants placed in extraction sockets, with spontaneous healing, or grafted with cortical porcine bone, or collagenated corticocancellous porcine bone. Materials and methods: Ninety patients in need for a single premolar/molar tooth extraction and an implant treatment were selected for the present study. Patients were randomly distributed among 3 groups: sites that healed naturally ( ctrl ), or sites that received ridge preservation with either cortical ( cort ) or collagenated corticocancellous porcine bone ( coll ). Three months after, all the experimental sites were reentered to insert implants. Marginal bone levels were recorded; soft tissues were analyzed and summarized with the Pink Esthetic Score (PES). Forty‐two patients out of 90 (initial cohort study) completed the entire follow‐up of 4 years. Results: Cumulative survival and success rates for all implants were 100% at a 4‐year evaluation. Mean marginal bone loss (MBL) was 1.14 ± 0.23 mm in the cort group, 1.13 ± 0.29 mm in the coll group, and 1.92 ± 0.07 mm in the ctrl group. There were no significant differences between the 2 grafting materials but MBL was significantly greater in the nongrafted sites ( P value < .001). The PES resulted significantly better (9.42 ± 0.75) for the cort group than for the coll group (8.53 ± 1.18) and ctrl group (6.07 ± 1.89) at 4‐year evaluation. Conclusions: Ridge preservation was more effective than natural healing in preserving marginal bone and in achieving better esthetic outcomes around implants 4 years after placement. The cortical porcine bone showed better clinical outcomes than collagenated corticocancellous porcine bone.